Antibacterial and Radiant Heat Absorbing Effects on TiO2 Based Resins - Budiprasojo, Azamataufiq; Erawantini, Feby; Mauquta, Lizam (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
TiO2 (Titanium dioxide) is widely used as a nanomaterial for bacterial decontamination processes. TiO2 can provide a more decontamination effect when exposed to UV light. Ultraviolet light can be a trigger for Tio2 nanoparticles to inhibit bacterial growth. The specimen we tested was a mixture of clear resin with TiO2 0.01gr - 0.06gr (0% -10% of specimen weight) with an increase of 0.01gr each. From the results of research conducted by our research team it was found that the decontamination effect of Escherichia coli bacteria persists even after exposure to ultraviolet light is eliminated. The specimen is also capable of absorbing sunlight and radiant heat with a consistent increasing trend for each increasing variation of the mixture.